2020
DOI: 10.1039/d0ra02646h
|View full text |Cite
|
Sign up to set email alerts
|

An approach to new chiral bicyclic imines and amines via Horner–Wadsworth–Emmons reaction

Abstract: New chiral cyclic imines and enamines were prepared via HWE reaction, with selectivity dependent on the carbonyl substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…To ensure that the obtained results are comparable, we also simulated the electronic and vibrational CD spectra at different levels of approximation; however, for the discussion here, we selected only the ones that demonstrate the best fit with the experimental spectra, i.e., obtained at the ωB97X-D/6–311+G(d,p) level of theory with the PCM solvent model. Additional motivation for using this approximation level was prior identification of its effectiveness and accuracy in reproducing chiroptical spectral features of various organic molecules of synthetic and natural origin [ 26 , 39 , 40 , 41 , 42 , 43 , 44 ]. In our previous work on β-lactams, we also showed that using the PCM solvent model significantly impacted the assignments’ credibility [ 22 , 31 , 33 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…To ensure that the obtained results are comparable, we also simulated the electronic and vibrational CD spectra at different levels of approximation; however, for the discussion here, we selected only the ones that demonstrate the best fit with the experimental spectra, i.e., obtained at the ωB97X-D/6–311+G(d,p) level of theory with the PCM solvent model. Additional motivation for using this approximation level was prior identification of its effectiveness and accuracy in reproducing chiroptical spectral features of various organic molecules of synthetic and natural origin [ 26 , 39 , 40 , 41 , 42 , 43 , 44 ]. In our previous work on β-lactams, we also showed that using the PCM solvent model significantly impacted the assignments’ credibility [ 22 , 31 , 33 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…We next examined the bases used in the Horner–Wadsworth–Emmons reaction (Table ). Sodium hydride used in the preliminary manufacturing route gave a good yield (entry 1), but it is not applicable for large-scale production due to safety concerns.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the use of bicyclic iminium salts has been reported for the asymmetric preparation of cyclic α-aminophosphonates 90 ( Scheme 17 ). Chiral cyclic imines 89 are synthesized from diamine 88 and ketoesters and their subsequent treatment in toluene with dialkyl phosphites gives tetrasubstituted α-aminophosphonates 90 in high yields and diastereoselectivities (78–95%, 68:32–98:2 dr) [ 51 , 52 ] . However, if imines 89 are activated with bromotrimethylsilane, they are supposed to form an iminium ion, which is reactive towards tris(trimethylsilyl) phosphite and then, α-aminophosphonic acid derivatives 91 can be obtained in high yields and diastereoselectivities (70–99%, 85:15–98:2 dr) [ 51 ].…”
Section: Diastereoselective Synthesis Of Tetrasubstituted α-Aminophosphonic Acid Derivativesmentioning
confidence: 99%